PERANCANGAN MEDIA PEMBELAJARAN INTERAKTIF MATA PELAJARAN IPA KELAS VI SD BERBASIS WEBSITE - Septiana Vratiwi; Efendi Efendi; Risma Wiwita; Taufik Abdul Hasan Amrullah (STKIP Pesisir Selatan, 2022)
Interactive learning media is one of the factors that can help the learning process to be more effective and efficient. Science for grade VI SD is one of the important subjects that can affect student graduation. Given the limitations of learning media in both the main book and the lecture method given by the teacher, it has not been 100% successful in making the material easily absorbable. The purpose of this research is to make the science learning process in grade VI SD more enjoyable through a media designed in such a way with an attractive interface design. The media is designed using a PHP programming language assisted by a UML (Unified Modeling language) system design tool to make it easier to visually represent the needs of the system. The results of this study produce a learning media in the form of a website that can be accessed by students anytime and anywhere without time constraints because this media is based online.